Consent in pregnancy: A qualitative study of the views and experiences of women and their healthcare professionals. (July 2019) - Nicholls, Jacqueline; David, Anna L; Iskaros, Joseph; Lanceley, Anne
Abstract: Objective: Consent in antenatal settings is contentious, poorly understood and recognised as problematic for pregnant women. This study aimed to investigate participants' views and experiences of the consent process. Design: Qualitative research performed in a large urban teaching hospital in London. Sixteen pregnant women and fifteen healthcare professionals (obstetricians and midwives) participated. Consent consultations were observed and in-depth interviews carried out with healthcare professionals and pregnant women using semi-structured interview guides. Data were collectively analysed to identify themes in the experiences of the consent process. Results: Four themes were identified: 1) Choice and shared decision-making. Pregnant women do not always experience consent in a choice-making way and often do not understand information provided to them. 2) Contextualising information disclosure. What is important to women is not only the information but the relational context in which consent is obtained. 3) Quality of HCP-woman relationship. Trust in their healthcare professional sometimes makes women seek less information and conversely. Individualised information is desired by women but professionals found it difficult to ensure that women receive this in practice. 4) Law and professional practice. Doctors are more aware of legal developments in consent related to the Montgomery case than their midwifery colleagues, but they are not always certain of the implications. Conclusion: Results suggest that an effective antenatal consent process which empowers pregnant women requires their understanding of provided information to be elicited. There is a delicate balance to be struck between the trust of a patient in their professional and information-based consent, rather than a simple focus on improving information provision. Whilst recognising women's desire for bespoke consent professionals acknowledged the difficulty of ensuring this in practice. If consent is to remain the legal yardstick of autonomous choice-making, women's understanding and that shared with their healthcare professional needs to be more explicitly addressed.